(untitled) (Altruism: The Indonesian Journal of Community Engagement, 2026)
The development of digital technology has opened up significant opportunities in the world of entrepreneurship, including for elementary school students. However, limited knowledge and skills in utilizing technology as a business tool remain a barrier. This community service activity aims to foster the entrepreneurial spirit of students at SDIT Adzkia Bangkinang through simple digital-based online sales training. The methods used included entrepreneurship socialization, training on the use of simple digital platforms such as WhatsApp and social media, and hands-on practice in product marketing. The results of the activity demonstrated an increase in students’ understanding of the concept of entrepreneurship, increased interest in entrepreneurship, and basic skills in online product promotion. This program contributes to developing independent, creative, and innovative characters in students from an early age.